(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
Skeletal scintigraphy is a highly sensitive tool in the detection of metastatic disease from prostate cancer, but its specificity is relatively low. Various quantitative parameters have been introduced to improve the bone scan specificity. Scintimetric method based Dr. V. Siva’s retention ratio is one such parameter proposed to help in predicting malignant or metastatic nature of the skeletal hot spots in a bone scan non-invasively. This study was performed to evaluate the V. Siva’s ratio in a small sample of prostate cancer patients in Bangladeshi population. This prospective observational study was carried out at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS) from July 2015 to June 2016. A total of 32 patients with diagnosed prostate cancer were enrolled. Each patient underwent two bone scans at 4 hours and 24 hours respectively after radiopharmaceutical injection. Focal hot spots reported by expert Nuclear Medicine specialists were identified in both scans and maximum counts were taken by drawing region of interest over the spots. Dr. V. Siva’s retention ratio was calculated by dividing the 4-hour count with 24-hour count. Finally statistical analysis was done. The mean V. Siva’s ratio of metastatic group was 9.3 ± 2.2 (95% CI 8.5-10.1) and that of degenerative group was 8.2 ± 2.0 (95% CI 7.5-8.9). Statistically significant difference was observed between the two groups. So it can be said that V. Siva’s retention ratio might be useful as a quantitative parameter in adjunct to conventional bone scintigraphy for the skeletal survey of carcinoma prostate patients. Bangladesh J. Nuclear Med. 20(1): 9-13, January 2017